Religious Beliefs and L2 Motivation in Islamic Schools: Integrating the L2 Motivational Self System with Islamic Identity - As Sabiq, Agus Husein (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examined how students’ religious beliefs relate to their motivation to learn English in four Islamic secondary schools in Central Java, Indonesia. Using a mixed-methods design, questionnaires were administered to 287 students, and semi-structured interviews were conducted with eleven purposively selected participants. Correlation analysis showed a significant positive relationship between religious beliefs and English learning motivation (r = .308, p .001), and regression analysis indicated that religious beliefs explained 9.5% of the variance in motivation (R² = .095). Qualitative findings revealed that students positioned English within Islamic concepts of lifelong knowledge-seeking (thalab al-‘ilm) and global Islamic communication (da’wah), viewing English as compatible with, and supportive of, their religious identity rather than as a threat. These results suggest that, in Islamic school contexts, religious beliefs can function as a motivational resource for learning English when appropriately acknowledged in pedagogy.